Decades of Quiet Diplomacy and Loud Decline South Africa’s Influence on Zimbabwe’s Democratic Path (1994-2014) - PETRICA, Dan (2021)
This book provides a detailed, critical radiography of Southern Africa by evaluating the democratization processes unfolding in two of the region’s most prominent states over the span of two decades.